Doing business in Spain - Kasianova, Anastasiia (2017)
The goal of the thesis is to examine the business environment in Spain, to trace how the economy was changing from the times of autarky until the current time. In addition, to find out what were the causes of the crisis and what Spain did in order to recover from it, to look at the legal framework of doing business in Spain